2023
DOI: 10.1051/0004-6361/202244678
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the X-ray reflection in low accretion-rate active galactic nuclei using XMM-Newton, NuSTAR, and Swift

Abstract: Context. An interesting feature of active galactic nuclei (AGN) accreting at low rates is the weakness of the reflection features in their X-ray spectra, which may result from the gradual disappearance of the torus with decreasing accretion rates. It has been suggested that low-luminosity AGN (LLAGN) would exhibit a different reflector configuration than high-luminosity AGN, covering a smaller fraction of the sky or simply having less material. Additionally, we note that the determination of the spectral index… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 138 publications
1
4
0
Order By: Relevance
“…This suggests that at low Eddington ratio, the average column density decreases. Diaz et al ( 2023 ) also found a similar relation between N tor H and λ Edd . The relation between N tor H and λ Edd also supports the Eddington ratio regulated unification and growth model (e.g.…”
Section: Obscuration Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…This suggests that at low Eddington ratio, the average column density decreases. Diaz et al ( 2023 ) also found a similar relation between N tor H and λ Edd . The relation between N tor H and λ Edd also supports the Eddington ratio regulated unification and growth model (e.g.…”
Section: Obscuration Propertiessupporting
confidence: 61%
“…Thus, we are unable to make a firm conclusion on the correlation/anticorrelation of λ Edd − . Recently, Diaz et al ( 2023 ) studied a sample of LLAGNs and found similar results. They argued that due to the small number of sources, they did not find a statistically significant correlation of -λ Edd .…”
Section: Dependence Of the Coronal Properties On The Eddington Ratiomentioning
confidence: 53%
“…A root cause is the considerable challenge to select and classify true low-accretionpower AGN, especially at high line-of-sight column densities. NuSTAR has provided an unprecedented view into the hard X-ray properties of the circum-nuclear environment of lowluminosity AGN for the first time (Ursini et al, 2015;Annuar et al, 2017;Young et al, 2018;Younes et al, 2019;Annuar et al, 2020;Diaz et al, 2020;Baloković et al, 2021;Diaz et al, 2023). NuSTAR has also led to the discovery and classification of a few low-luminosity Compton-thick AGN (Annuar et al, 2017;Brightman et al, 2018;Da Silva et al, 2021), providing exciting evidence that suggests AGN can sustain a significant obscuration structure at low luminosities.…”
Section: The Circum-nuclear Obscurer Of Agn At Low Accretion Powermentioning
confidence: 99%
“…It should be stressed that in stage 1, the covering factors could actually be lower than what was inferred here due to our AGN selection, which is missing AGN that accrete at very low Eddington ratios (log 4 Edd l < -). In fact, besides showing little absorption (see also She et al 2018), AGN accreting at very low λ Edd also typically display faint reflection features (e.g., Ptak et al 2004;Bianchi et al 2017;Diaz et al 2020Diaz et al , 2023Jana et al 2023;see Ho 2008 for a review of the subject).…”
Section: Radiation-regulated Smbh Growthmentioning
confidence: 99%